Step
*
1
2
2
of Lemma
int-to-ring-add
1. r : Rng
2. a1 : ℤ
3. a2 : ℤ
4. ∀x:ℤ. (int-to-ring(r;x + 1) = (int-to-ring(r;x) +r 1) ∈ |r|)
5. ∀x:ℤ. (int-to-ring(r;x - 1) = (int-to-ring(r;x) +r (-r 1)) ∈ |r|)
⊢ int-to-ring(r;a1 + a2) = (int-to-ring(r;a1) +r int-to-ring(r;a2)) ∈ |r|
BY
{ xxx((Assert ⌜∀n:ℕ. ∀x:ℤ.  (|x| < n 
⇒ (∀y:ℤ. (int-to-ring(r;x + y) = (int-to-ring(r;x) +r int-to-ring(r;y)) ∈ |r|)))⌝⋅
      THENM (InstHyp [⌜|a1| + 1⌝;⌜a1⌝;⌜a2⌝] (-1)⋅ THEN Auto)
      )
      THEN InductionOnNat
      THEN Auto')xxx }
1
1. r : Rng
2. a1 : ℤ
3. a2 : ℤ
4. ∀x:ℤ. (int-to-ring(r;x + 1) = (int-to-ring(r;x) +r 1) ∈ |r|)
5. ∀x:ℤ. (int-to-ring(r;x - 1) = (int-to-ring(r;x) +r (-r 1)) ∈ |r|)
6. n : ℤ
7. 0 < n
8. ∀x:ℤ. (|x| < n - 1 
⇒ (∀y:ℤ. (int-to-ring(r;x + y) = (int-to-ring(r;x) +r int-to-ring(r;y)) ∈ |r|)))
9. x : ℤ
10. |x| < n
11. y : ℤ
⊢ int-to-ring(r;x + y) = (int-to-ring(r;x) +r int-to-ring(r;y)) ∈ |r|
Latex:
Latex:
1.  r  :  Rng
2.  a1  :  \mBbbZ{}
3.  a2  :  \mBbbZ{}
4.  \mforall{}x:\mBbbZ{}.  (int-to-ring(r;x  +  1)  =  (int-to-ring(r;x)  +r  1))
5.  \mforall{}x:\mBbbZ{}.  (int-to-ring(r;x  -  1)  =  (int-to-ring(r;x)  +r  (-r  1)))
\mvdash{}  int-to-ring(r;a1  +  a2)  =  (int-to-ring(r;a1)  +r  int-to-ring(r;a2))
By
Latex:
xxx((Assert  \mkleeneopen{}\mforall{}n:\mBbbN{}.  \mforall{}x:\mBbbZ{}.
                              (|x|  <  n  {}\mRightarrow{}  (\mforall{}y:\mBbbZ{}.  (int-to-ring(r;x  +  y)  =  (int-to-ring(r;x)  +r  int-to-ring(r;y)))))\mkleeneclose{}
          \mcdot{}
        THENM  (InstHyp  [\mkleeneopen{}|a1|  +  1\mkleeneclose{};\mkleeneopen{}a1\mkleeneclose{};\mkleeneopen{}a2\mkleeneclose{}]  (-1)\mcdot{}  THEN  Auto)
        )
        THEN  InductionOnNat
        THEN  Auto')xxx
Home
Index